A model for studying the effect of applying international financial reporting standards on the quality of financial reports by applying to commercial banks in the Gaza Strip, Palestine - Al khozondar, Ayah Jarallah; Zedan Ibrahim, Mohamed (Journal of Research in Finance and Accounting, 2020)
The research aimed to examine the effect of applying the IFRS standards on the quality of financial reports by studying income-generating behavior and instructing the signal using a measure of loan loss provision and measuring profit fluctuations. The sample consisted of the commercial banks listed in the Palestinian capital market which were obligated to adopt the international financial reporting standards. Research data were collected from financial reports. For the purposes of statistical analysis, multiple linear regression analysis, stepwise linear regression analysis, Pearson correlation analysis, ANOVA variance analysis, and Levin analysis were used to equal contrast. The results indicated that the banks' compliance with the international financial reporting standards leads to reducing the introduction of income through the provision for loan losses compared to the pre-commitment period. Pre-obligatory, and the results did not support the hypothesis that banks ’commitment leads to increased volatility of profits compared to the pre-obligatory period.